TOURISM COMMUNICATION IN INDONESIA SOCIAL MEDIA - Nela Widiastuti (SENGKUNI Journal (Social Science and Humanities Studies), 2020)
Melaka is known to have historical values, even the beginning of the birth of Malaysia began in this country. Melaka is also known as the main maritime trade center in this region precisely in the 16th century. Traders from various countries such as Arab, China, India and Europe also came to Malacca to trade silk, spices, gold and porcelain. Therefore on July 7, 2008 UNECSO recognized Melaka as a World Heritage City State together with Georgetown, the State of Penang. Now, Melaka is here to offer a variety of tourism products based on 13 Tourism Product Sub-Sectors, including History, Culture, Recreation, Sports, Shopping, Conventions, Health, Education, Agro Tourism, Culinary, Melaka My Second House, Youth Tourism and Ecotourism. With the theme "Touring Historical Melaka Means Visiting Malaysia" and "Melaka Bandaraya Melaka UNESCO World Heritage" Melaka offers a variety of cultural uniqueness such as Malay, Chinese, Indian, Portuguese, Peranakan, Chitti and others. To further enhance the Melaka tourism industry, the Melaka State Government took the initiative to launch Visit Melaka Year 2019 (VMY 2019) which aims to showcase the culture and uniqueness of Melaka through "Melaka A Gateway to Historic Malaysia". This research explores forms of tourism communication in the 2019 Melaka Visit Program launched by the government, Malaysia, with a case study on tourists. This research uses a qualitative approach with a case study method. Research data collection using interview methods, involved observation and literature study. The purpose of this study was to determine the effectiveness of the Melaka tourism communication strategy launched by the government, through a number of communication channels, one of them through social media. The results showed that social media has a significant role in creating emotional experiences about the tourist attractions they visit..